Effect of preoperative Staphylococcus aureus screening / decolonization on surgical site infection following major othopaedic operations: a prospective study - Abou El-khier, Noha Tharwat; Elganainy, Abd Elrahman Ahmad (International Journal of Infection Control, 2016)
Background: Carriers of Staphylococcus aureus (S. aureus) have a higher likelihood of having surgical site infection (SSI). Aim: evaluate the impact of preoperative S. aureus screening and decolonization on the rate of SSI after major orthopaedic surgical operations. Methods: A prospective observational study was conducted on 400 patients scheduled for major orthopaedic surgical procedures at our institution between December 2013 to December 2014. The enrolled patients were divided into: intervention group (250 patients) who underwent the screening / decolonization protocol, and a control group (150 patients) with no implementation of the protocol. All patients were followed up for 3 months for postoperative S. aureus SSI. Findings: Of the 250 patients screened, 70 (28%) had positive nasal swabs for S. aureus. Among screened patients, 58 (23.2%) were identified as MSSA carriers, and 12 (4.8%) were identified as MRSA carriers. On post operative follow up, there were a total of 5 S. aureus SSI in the control group (3.3%, 95% CI 1.1-7.6%) and 3 in the intervention group (1.2%, 95% CI 0.25- 3.5% ). There was 2 MRSA infection in the control group (1.3%, 95% CI 0.2-4.7%), one MRSA infection in the intervention group (0.4%, 95% CI 0.01-2.2). Screening and decolonization lowered, the S. aureus SSI rate to 1.2% in screened/decolonized (intervention) versus 3.3% in those unscreened (control) patients. Conclusion: preoperative screening / decolonization of MRSA and MSSA carriers among patients undergoing major orthopaedic surgical operations using a combination of mupirocin and chlorhexidine is a safe protocol for reducing S. aureus SSI.